2017
DOI: 10.14204/ejrep.32.13076
|View full text |Cite
|
Sign up to set email alerts
|

La Motivación en la Resolución de Problemas Aritmético-algebraicos. Un Estudio con Alumnado de Educación Secundaria

Abstract: Introducción. La motivación constituye un factor importante en el aprendizaje de las matemáticas. Dentro de este ámbito educativo, la resolución de problemas ocupa un lugar central en la mayoría de currículos de matemáticas en Educación Secundaria. El objetivo de esta investigación es detectar las diferencias en motivación en función de las estrategias empleadas para la resolución de problemas aritmético-algebraicos.Método. Se han analizado los procedimientos de resolución de tres problemas verbales aritmético… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
(42 reference statements)
0
4
0
1
Order By: Relevance
“…Considerable empirical support for the relation between Expectancy-value beliefs and student engagement can be found for Secondary Education [58][59][60] and University students [61,62], which confirms that beliefs are significant predictors of engage-ment. The results of some studies show that Expectancy-value beliefs strongly influence performance, whereas the subject value of a task considerably impacts choice, effort, and persistence [63,64].…”
Section: Support Resources and Expectancy-value Beliefs And Student Engagementmentioning
confidence: 99%
“…Considerable empirical support for the relation between Expectancy-value beliefs and student engagement can be found for Secondary Education [58][59][60] and University students [61,62], which confirms that beliefs are significant predictors of engage-ment. The results of some studies show that Expectancy-value beliefs strongly influence performance, whereas the subject value of a task considerably impacts choice, effort, and persistence [63,64].…”
Section: Support Resources and Expectancy-value Beliefs And Student Engagementmentioning
confidence: 99%
“…Research has shown that competence beliefs are related positively to several different dimensions of value within a specific domain, but that the relations involving intrinsic value seem to be the strongest . In crosssectional and longitudinal studies, there is growing evidence of expectancy beliefs having a strong influence on achievement, while value beliefs have stronger influence on choice, effort, and persistence in achievement-related activities (Gasco & Villarroel, 2014;Marsh, Trautwein, Lüdtke, Köller, & Baumert, 2005;Nagengast et al, 2011;Trautwein et al, 2012).…”
Section: Expectancy-value Theorymentioning
confidence: 99%
“…Recent cross-sectional and longitudinal studies have found that expectancy beliefs strongly influence achievement, whereas subject value considerably impacts choice, effort and persistence (Nagengast et al, 2011; Gasco and Villarroel, 2014; Guo et al, 2015). …”
Section: Introductionmentioning
confidence: 99%